CLASSIFICATION OF ANXIETY DISORDERS COMORBID WITH MAJOR DEPRESSION: COMMON OR DISTINCT INFLUENCES ON RISK?. Issue 2 (29th September 2015) - Moscati, Arden; Flint, Jonathan; Kendler, Kenneth S.
Abstract : Background: Anxiety and depression display frequent comorbidity. Individuals with comorbid disorders also often have more extreme symptomatology than those with single disorders. This correlation between comorbidity and severity poses an interesting question: Are comorbid forms of anxiety and depression essentially just more severe versions of the pure disorders? Methods: In a large major depression (MD) case–control sample of individuals from the China, Oxford and VCU Experimental Research on Genetic Epidemiology project, we examined the patterns of lifetime anxiety comorbidity (including generalized anxiety disorder—GAD, panic disorder, and five phobia subtypes) among MD cases ( N = 5, 864) in this population. Binary and multinomial logistic regression was used to estimate associations between risk factors and outcomes including MD as well as latent class membership, which were compared using continuation ratios. Results: We found a five‐class solution to fit best, and each resulting class had a distinct pattern of association with the tested risk factors. The use of continuation ratios suggests that a class characterized by high endorsement of GAD is comparable to a more severely affected "pure MD" group. The other three classes (characterized by agoraphobia, various specific phobias, and by high endorsement of all comorbid anxiety disorders, respectively) appear to differ meaningfully from MD alone. Conclusions: Risk for MD resulting from environmental and psychosocial factors may also predispose individuals to GAD, and less consistently, other anxiety disorders. Presentations of MD with certain phobias display distinguishably different patterns of risk, however, and are therefore likely qualitatively distinct.